The impact of PROP and thermal taster status on the emotional response to beer - Yang, Qian; Dorado, Rocio; Chaya, Carolina; Hort, Joanne (Elsevier, 2018)
With an increasingly competitive global market, understanding consumer emotional response to products can provide a different perspective to identify drivers of consumer food choice behaviour beyond traditional hedonic measurement. This study investigated how two taste phenotypes (Thermal taster status (TTS) and PROP taster status (PTS)) impacted liking and emotional response to beers varying in bitterness, carbonation and serving temperature. Volunteers (n = 60, balanced for TTS and PTS) were invited to express their liking and emotional response to 2 commercial beers of contrasting bitterness, presented at two different carbonation levels (commercial carbonation and low carbonation level) and served at two temperatures (cold and ambient). In general, when beers were served at their commercial carbonation level and at a cold temperature, they received higher liking scores and evoked more positive emotions and less negative emotions. Signficant temperature ∗ carbonation interactions were found for liking and some emotion categories. At commercial carbonation levels, cold beer was better liked and evoked more positive emotions than beer served at ambient temperature, but no such temperature effect was observed at the low carbonation level. Although the sample size was relatively small, significant effects for liking were observed for PTS but not TTS, suggesting PTS is a more influential factor regarding liking than TTS. However, thermal tasters (TT) rated 6 out of 10 emotion categories significantly higher for beer than thermal non-tasters (TnT), indicating emotional response may be more sensitive to capture the differences across taste phenotypes than liking, and that TT show increased negative emotions to beer in general. PROP supertasters (ST) rated some emotion categories significantly higher than non-tasters (NT) and, in contrast to TTS these were the more positive emotions, such as excited and content. This is the first study to report an impact of both TTS and PTS on emotional response. Furthermore, this study observed significant relative effects of TTS and PTS on emotional response, where the effect of PTS was more pronounced in TnT. This highlights the importance of investigating the combined effects of different phenotypes on consumer response representing the reality of different consumer segments.